Development of subjective well-being inventory in schools using the RASCH model - Humairah Azzahrah; Ahman Ahman; Nur Fadhilah Umar (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2024)
This study aims to develop an inventory to measure subjective well-being among high school (SMA) and vocational high school (SMK) students in Indonesia. Using Item Response Theory (IRT with the Rasch model and Winstep software, it adopts a mixed methods design, specifically an exploratory sequential approach. Purposive sampling selects 350 participants from 16 schools in West Java, Sulawesi, and Sumatra. The inventory comprises 60 statement items across three components: pleasant affect, unpleasant affect, and life satisfaction, totaling 16 indicators. Modified Likert scales assess each item. Validation involves validators expert guidance counseling, and Rasch modeling analysis covering item fit, dimensionality, and reliability. The research findings indicate that the development of the Indonesian version of the subjective well-being inventory for high school/vocational high school students using the Rasch modeling approach has successfully produced a valid and reliable measurement tool. The analysis results show that this inventory meets the criteria for item fit, inventory dimensionality, and person and item reliability